Acute‐on‐chronic liver failure: Where do we stand?. (21st June 2021) - Durand, François; Roux, Olivier; Weiss, Emmanuel; Francoz, Claire
Abstract: Acute‐on‐chronic liver failure (ACLF) is defined by the rapid development of organ(s) failure(s) associated with high rates of early (28‐day) mortality in patients with cirrhosis. ACLF has been categorized into three grades of increasing severity according to the nature and number of organ failures. In patients with grade 3 ACLF, 28‐day mortality is >70%. While the definition of ACLF has been endorsed by European scientific societies, North American and Asian Pacific associations have proposed alternative definitions. A prognostic score called the CLIF‐C ACLF score provides a more precise assessment of the prognosis of patients with ACLF. Although bacterial infections and variceal bleeding are common precipitating factors, no precipitating factor can be identified in almost 60% of patients with ACLF. There is increasing evidence that cirrhosis is a condition characterized by a systemic inflammatory state and occult infections or translocation of bacteria or bacterial products from the lumen of the GUT to the systemic circulation which could play a role in the development of ACLF. Simple and readily available variables to predict the occurrence of ACLF in patients with cirrhosis have been identified and high‐risk patients need careful management. Whether prolonged administration of statins, rifaximin or albumin can prevent ACLF requires further study. Patients with organ(s) failure(s) may needed to be admitted to the ICU and there should be no hesitation in admitting patients with cirrhosis to the ICU. No benefit to survival was observed with albumin dialysis and rescue transplantation is the best option in the most severe patients. One‐year post‐transplant survival rates exceeding 70%‐75% have been reported, including in patients with grade 3 ACLF but these patients were highly selected. Criteria have been proposed to define futile transplantation (too ill to be transplanted), but these criteria need to be refined to include age, comorbidities and frailty in addition to markers of disease severity.